2007
DOI: 10.1016/j.foodcont.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial effect of wine on Listeria innocua in a model stomach system

Abstract: A model stomach, containing a food matrix and a synthetic gastric Xuid, was used to study the bactericidal eVect of ingested wine on Listeria innocua. Volumes of wine equivalent to the ingestion of one glass and half a bottle, led, over a period of less than 2 h, to a reduction of 3 and 4 logarithmic cycles of the initial population respectively. The inXuence of ethanol and organic acids, wine constituents with known antimicrobial properties, was investigated. Ethanol exhibited a higher bactericidal eVect than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…Various in vitro studies indicated that the potency of wine as an antibacterial agent was higher than ethanolic solutions at concentrations equivalent to the wine (Just & Daeschel, 2003;Weisse et al, 1995). Fernandes et al (2007) reported that malic acid and lactic acid were amongst the most effective organic acids in the inactivation of Listeria inocua NCTC 11288. Moretro and Daeschel (2004) found that the combination of organic acids (malic and tartaric) with ethanol (15%) and low pH ( 3.0) had significantly stronger antimicrobial activity than the sum of the individual effects of these components against various food-borne pathogens, indicating potential synergistic interactions.…”
Section: Survival Of B Cereus Vegetative Cells and Spores In Wine Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Various in vitro studies indicated that the potency of wine as an antibacterial agent was higher than ethanolic solutions at concentrations equivalent to the wine (Just & Daeschel, 2003;Weisse et al, 1995). Fernandes et al (2007) reported that malic acid and lactic acid were amongst the most effective organic acids in the inactivation of Listeria inocua NCTC 11288. Moretro and Daeschel (2004) found that the combination of organic acids (malic and tartaric) with ethanol (15%) and low pH ( 3.0) had significantly stronger antimicrobial activity than the sum of the individual effects of these components against various food-borne pathogens, indicating potential synergistic interactions.…”
Section: Survival Of B Cereus Vegetative Cells and Spores In Wine Anmentioning
confidence: 99%
“…Several studies demonstrate the antibacterial properties of wine against relevant food-borne pathogenic bacteria (Carneiro, Couto, Mena, Queiroz, & Hogg, 2008;Correia et al, 2003;Fernandes, Gomes, Couto, & Hogg, 2007;Moretro & Daeschel, 2004;SugitaKonishi, Hara-Kudo, Iwamoto, & Kondo, 2001;Waite & Daeschel, 2007;Weisse, Eberly, & Person, 1995). Weisse et al (1995) reported that red and white wines were able to reduce the viability of several bacteria responsible for traveller's diarrhoea by 5e6 log cycles in 20 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, it has been shown that wine and some of its components are effective against some gastrointestinal pathogens such as E. coli, Salmonella, Listeria, Shigella, and Helicobacter pylori (Just & Daeshchel, 2003;Romero, Medina, Vargas, Brenes, & De Castro, 2007;Bellido et al, 1996;Brenner, Rothenbacher, Bode, & Adler, 1999;Fernández, Gomes, Couto, & Hogg, 2007;Mahady, Pendland, & Chadwick, 2003;Marimon, Bujanda, Gutiérrez-Stampa, Cosme, & Arenas, 1998;Sheth et al, 1988) and it has been proposed that the digestive qualities of wine are to a great extent the result of its antibacterial properties (Weisse et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…than a physiological saline solution adjusted to the same pH, supporting the antibacterial role of other components of this fluid. The antibacterial effect of wine in model stomach systems, simulating the consumption of wine during a meal, has been demonstrated for E. coli O157:H7, Salmonella typhimurium (Just & Daeschel, 2003) and Listeria innocua (Fernandes, Gomes, Couto, & Hogg, 2007).…”
Section: Introductionmentioning
confidence: 99%